2022
DOI: 10.3390/plants11121530
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Synthesis of Foreign Nuclear Protein Stimulates Viral Reproduction via the Induction of γ-Thionin Expression

Abstract: Plants are a promising platform for recombinant protein production. Here we propose a novel approach to increase the level of viral vector-mediated recombinant protein synthesis. This approach is based on the hypothesis that antiviral protection is weakened during the antibacterial cellular response. We suggested that introduced to the cell foreign nuclear localized proteins, including effectors such as bacterial nucleomodulins, can interfere with the import of cellular nuclear proteins and launch antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…To test this assumption, we obtained recombinant 6xHis-NbMIG21 in Escherichia coli cells and performed in vitro binding of this protein with different promoter regions, analyzing the results using a gel retardation assay ( Figure 11 ). We used sequences of several available promoters of various N. benthamiana genes, including PrKPILP [ 38 ], PrThio [ 39 ], PrNtPME, and PrAELP [ 21 ], cauliflower mosaic virus 35S promoter and identified in this work PrMIG21, expecting that promoters contain common regulatory elements, which may be important for NbMIG21p binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this assumption, we obtained recombinant 6xHis-NbMIG21 in Escherichia coli cells and performed in vitro binding of this protein with different promoter regions, analyzing the results using a gel retardation assay ( Figure 11 ). We used sequences of several available promoters of various N. benthamiana genes, including PrKPILP [ 38 ], PrThio [ 39 ], PrNtPME, and PrAELP [ 21 ], cauliflower mosaic virus 35S promoter and identified in this work PrMIG21, expecting that promoters contain common regulatory elements, which may be important for NbMIG21p binding.…”
Section: Resultsmentioning
confidence: 99%
“…But the side effect of this cellular reaction is sensitivity to the virus: viral vector reproduction is stimulated both upon a γ-thionin elevated expression and massive synthesis of foreign NLS-containing proteins. The exact mechanism of these effects is unknown, but it likely involves interference with nucleocytoplasmic transport [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…And it is not the only example of balancing between resistance and susceptibility: recently it was shown that increased production of NLS-containing proteins (as a mimetic of nucleomodulins) in plant cell leads to the induction of γthionin, a factor of antibacterial defense response, but the side effect of this cellular reaction is sensitivity to the virus -viral vector reproduction is stimulated both upon γ-thionin elevated expression or massive synthesis of foreign NLS-containing proteins. The exact mechanism of these effects is unknown but likely it involves interference with nucleocytoplasmic transport [40].…”
Section: Discussionmentioning
confidence: 99%
“…To test this assumption, we obtained recombinant 6xHis-MIG21 in Escherichia coli cells and performed in vitro binding of this protein with different promoter regions analyzing results by gel retardation assay (Figure 10). We used sequences of several available promoters of various N. benthamiana genes including PrKPILP [39], PrThio [40], PrNtPME and PrAELP [21], and identified here PrMIG21 as well as cauliflower mosaic virus 35S promoter, expecting that promoters contain common regulatory elements, which may be important for NbMIG21 binding.…”
Section: Nbmig21 Interacts With Promoter Regions In Vitromentioning
confidence: 99%